2014
DOI: 10.1371/journal.pone.0087926
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Non-Steatotic Hepatic Fat Fractions on Quantitative Diffusion-Weighted Imaging of the Liver

Abstract: Diffusion-weighted imaging (DWI) is an important diagnostic tool in the assessment of focal liver lesions and diffuse liver diseases such as cirrhosis and fibrosis. Quantitative DWI parameters such as molecular diffusion, microperfusion and their fractions, are known to be affected when hepatic fat fractions (HFF) are higher than 5.5% (steatosis). However, less is known about the effect on DWI for HFF in the normal non-steatotic range below 5.5%, which can be found in a large part of the population. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…In contrast to a previously reported study in a fat-water mixed phantom (12), our simulations and in vivo observations suggested that underestimation of renal diffusion coefficients may be significant even at low fractions of the fat signal, and the rate of underestimation decreases until the curve nearly plateaus. Dijkstra et al showed that the correlation of pure-diffusivity and FRF is stronger using a log-linear compared to linear correlation (14), concordant with our observed correlation of this marker and Oil-Red-O. Taken together, these findings support a non-linear relationship between the FRF and pure-diffusivity (28).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast to a previously reported study in a fat-water mixed phantom (12), our simulations and in vivo observations suggested that underestimation of renal diffusion coefficients may be significant even at low fractions of the fat signal, and the rate of underestimation decreases until the curve nearly plateaus. Dijkstra et al showed that the correlation of pure-diffusivity and FRF is stronger using a log-linear compared to linear correlation (14), concordant with our observed correlation of this marker and Oil-Red-O. Taken together, these findings support a non-linear relationship between the FRF and pure-diffusivity (28).…”
Section: Discussionsupporting
confidence: 91%
“…The confounding effect of fat on hepatic DWI parameters has been suggested by several recent studies, demonstrating an inverse correlation of ADC and pure-diffusivity with fat content (13, 15), and its significance emphasized even in non-steatotic livers (14). In contrast to a previously reported study in a fat-water mixed phantom (12), our simulations and in vivo observations suggested that underestimation of renal diffusion coefficients may be significant even at low fractions of the fat signal, and the rate of underestimation decreases until the curve nearly plateaus.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, when taking the minimal ADC value of the ROI, they observed significant differentiation between glioma grades by the ADC, which is in accordance with our results. In addition, other compounds, such as fatty acids and calcifications, potentially present in oligodendroglioma, can affect the minimal ADC of a tumor which can be avoided by a manually selected area of low diffusion with a circle ROI (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the published results on IVIM-derived PF of steatotic livers. Most of papers reported elevated PF (9), a small portion of papers(17) reported PF similar to normal liver which also indicate PF was artificially elevated since steatotic livers should have reduced true PF.…”
mentioning
confidence: 99%